2021
DOI: 10.1055/s-0041-1731944
|View full text |Cite
|
Sign up to set email alerts
|

Clostridioides difficile Diarrhea: An Emerging Problem in a South Indian Tertiary Care Hospital

Abstract: Context Clostridioides difficile infection (CDI) is one of the most common infectious causes of hospital-acquired diarrhea. The actual burden of the disease is underestimated in India due to inadequate diagnostic methods and limited studies conducted. Aims The aim of this study was to determine the burden and risk factors of CDI among patients with hospital-acquired diarrhea. Methods and Materials Stool specimen of patients (age > 1 year) with hospital-acquired diarrhea were screened for glutamate dehydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Colonization and infection with CD can also be stimulated by acid suppression due to usage of PPI. 16 In our study,18 out of 32 patients were on PPI. This could also have promoted the development of CDI in these patients.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Colonization and infection with CD can also be stimulated by acid suppression due to usage of PPI. 16 In our study,18 out of 32 patients were on PPI. This could also have promoted the development of CDI in these patients.…”
Section: Discussionmentioning
confidence: 79%
“…This was similar to the study done by Segar et al where the prevalence of CDI was 4%. 14 3,15,16 The reason for the lower prevalence could be due to the adhesion to the antibiotic policy adopted in our hospital and strict implementation of infection control practices.…”
Section: Discussionmentioning
confidence: 99%
“…This variation in prevalence can be attributed to the dissimilar study population characteristics and the variation in the testing algorithm used in different studies; those that used molecular techniques for the detection of CDI had a higher prevalence, as shown by Kannambath et al who observed an increase from 12 to 18.68% in prevalence by using molecular assays. 29 Although these molecular assays have increased sensitivity they may lead to overdiagnosis of CDI because they only detect the toxin gene which may or may not be functional to produce toxin/disease in patients.…”
Section: Discussionmentioning
confidence: 99%
“…8 A 2021 study from a tertiary care center in south India showed the prevalence of CDAD in cancer patients to be 18.67%. 9 Due to the lack of large-scale data and multicentric studies, the true burden of this problem is unknown in India. Lack of uniform availability of testing infrastructure as well as access to therapy is among the challenges faced in Indian settings.…”
Section: Introductionmentioning
confidence: 99%
“…8 A 2021 study from a tertiary care center in south India showed the prevalence of CDAD in cancer patients to be 18.67%. 9…”
Section: Introductionmentioning
confidence: 99%